Effects of copper and zinc on proteoglycan metabolism in articular cartilage - M. Pasqualicchio; R. Gasperini; G. P. Velo; M. E. Davies (Mediators of Inflammation)
Co-Cultures of porcine articular cartilage and synovium or synovial conditioned medium were used as an in vitro model to mimic inflammatory events at the cartilage/synovial junction in degenerative joint disease. This model provides a useful tool to assess the anti-inflammatory and antiarthritic properties of pharmacological agents. In this study the effects of copper and zinc on (i) PG synthesis by cartilage and (ii) synovial-induced PG depletion have been investigated. Copper sulphate at a concentration of 0.01 mM did not stimulate PG synthesis significantly in cultured cartilage explants but completely abrogated the inhibitory effects of synovial tissue in co-culture experiments. This finding was supported by the histological demonstration of copper-dependent reversal of the PG depletion in cartilage exposed to synovial conditioned medium. Zinc sulphate at 0.01 mM had no effect on PG synthesis and was unable to protect cartilage against synovialinduced PG depletion. These results reveal possible mechanisms by which copper exerts its anti-inflammatory and anti-arthritic actions.